ANALISIS KONDISI FISIK ATLET PETANQUE UNDIKMA TAHUN 2020 - Muhammad Irvan Zuhri; Isyani Isyani; Fitri Anggaraeni Ariyanto (Universitas Pendidikan Mandalika, 2020)
This study aims to determine the physical condition of UNDIKMA petanque athletes in 2020. This type of research is a quantitative descriptive study with data collection techniques using survey methods. The subjects were UNDIKMA petanque athletes, consisting of 7 male and 3 female athletes. The physical condition instruments used were tests: arm muscle strength, hand eye coordination, wrist flexion, grip strength or hand feel, arm muscle power and balance. The data obtained for each test item is raw data then converted into t-score values and then the data is interpreted by categorizing the data. Based on the results of the study it can be concluded that the physical condition of UNDIKMA petanque athletes in 2020 was 1 athlete (14.3%) in the excellent category, 3 athletes (42.8%) in the moderate category, 2 athletes (28.6%) in the poor category and 1 athlete (14.3%) in the very poor category. So it can be concluded that the physical condition of UNDIKMA petanque athletes in 2020 is in the medium category